SYSTEMATIC LITERATUR REVIEW (SLR): PERAN KURIKULUM PENDIDIKAN TINGGI DALAM MEMBANGUN KOMPETENSI GLOBAL MAHASISWA DI ERA DIGITAL - Farel Taba; Hafid Rahmandan; Sugeng Pramudibyo; Muhammad Yasser Arafat (Universitas Negeri Gorontalo, 2025)
This study aims to systematically examine how the Curriculum course contributes to developing students’ global competencies in the digital era. Through a Systematic Literature Review (SLR) approach, this study analyzes various scholarly articles from Google Scholar (2021–2025), research reports, and academic publications relevant to curriculum integration, global competence development, and the demands of 21st-century higher education. The review findings indicate that the Curriculum course not only provides conceptual understanding of curriculum design, implementation, and evaluation, but also encourages students to develop critical thinking skills, digital literacy, cross-cultural collaboration, and global problem-solving abilities. The use of educational technology and innovative learning models further strengthens the development of global competencies by providing more interactive and contextual learning experiences, making the Curriculum course an increasingly important and evolving strategy in the digital era.